Night View of World's Fair Grounds from Observation Platform of Sky Ride (Max Rigot Selling Co)
View looking south from the observation platform of the Sky Ride. The buildings in the distance include the Travel and Transport and General Motors Buildings, with Chicago's famous Outer Drive to the right and Lake Michigan on the left.